HBV co-infection is associated with persistently elevated liver stiffness measurement in HIV-positive adults: A 6-year single-centre cohort study in Nigeria. Issue 6 (November 2021) - Rivera, Adovich S; Machenry, Stephen; Okpokwu, Jonathan; Olatunde, Bola; Ugoagwu, Placid; Auwal, Muazu; Sule, Halima; Agaba, Patricia; Agbaji, Oche O; Thio, Chloe L; Murphy, Robert Leo; Hawkins, Claudia
Background: In Nigeria, the effect of Hepatitis B virus (HBV) on long-term liver outcomes in persons with HIV (PLH) has not been described. We determined changes in liver stiffness measure (LSM) using transient elastography over 6 years in HIV mono-infected and HIV-HBV co-infected Nigerians initiating antiretroviral therapy (ART) and factors associated with LSM decline. Methods: This single centre, cohort study enrolled ART-naïve HIV mono- and HIV-HBV co-infected adults (≥18 years) at the APIN Public Health Initiatives–supported HIV Care and Treatment Centre at Jos University Teaching Hospital, Nigeria, from 7/2011 to 2/2012. LSM at baseline, Years 3 and 6 were analysed using longitudinal models to estimate changes over time and their predictors. Results: Data from 100 (31%) HIV-HBV co-infected and 225 (69%) HIV mono-infected participants were analysed. Median LSM at baseline was 6.10 (IQR: 4.60–7.90) kPa in co-infected and 5.10 (IQR: 4.40–6.10) kPa in mono-infected participants. In adjusted analyses, average LSM was not significantly different between Year 0 and 3 (β = 0.02, −0.22 to 0.26, p = 0.87 and Year 0 and 6 (β = −0.02, −0.23 to 0.27, p = 0.88) in both groups ( p >0.05), but co-infected participants had significantly higher LSM than mono-infected throughout follow-up (β = 0.018, 0.019–0.28, p < 0.001). Year 3 LSM differed according to ART initiation status by Year 3 (initiators - non-initiators: −0.87, −1.70 to −0.29). Conclusion: In this cohort, LSM remained higher among HIV-HBV co-infected versus HIV mono-infected participants throughout follow-up. Our findings emphasize the continuing need for monitoring of liver outcomes in HIV-HBV co-infected populations on ART and the importance of preventing HBV infection among PLH to optimize liver health.